Generadores de números primos y factorizadores de números compuestos - Bulat, Mijail (2006)
The sequence of natural numbers presents itself as a multidimensional array. Two problems are solved on the basis of these arrays:a) distribution of prime numbers in multidimensional array,b) factoring of composite numbers.For solving the problems related to the distribution of prime numbers, there was developed a generator of prime numbers in the Delphi programming language. The program serves as well as a generator of Mersenne composite numbers. While generating a Mersenne composite number, one of its divisors is automatically defined.The problem of factoring in Delphi is solved for numbers of the form 2i -1, where i is a natural number. Mersenne composite numbers are factoring in particular for the prime i.